The effectiveness of social recreational games on the psychological skills of wheelchair tennis players - Hamzah, Marwah Ali (Tanjungpura Journal of Coaching Research, 2026)
Background. Visualization, attention control, self-confidence, relaxation, anxiety management, and achievement motivation are among the main psychological skills needed to play wheelchair tennis. Several approaches emphasize training methods while preparing disabled athletes; however, they focus primarily on technical skills and physical preparation, giving scant consideration to psychological preparation. Adapted sports players can improve their psychological skills by playing social recreational games within a stimulating environment in addition to not losing their motivation. Objectives. The purpose of this paper is to develop social recreational games for wheelchair tennis players, identify the current state of psychological skills among wheelchair tennis players, and determine the impact of social recreational games on these skills. Methods. An experimental approach was used with two equivalent groups and pretest–posttest design. The study population was 13wheelchair players in the Al-Majd Iraqi Federation team during the season (2024–2025). Twelve players were randomly allocated to two groups; an experimental group (n = 6) and control group (n = 6). The dependent variable was players’ psychological skills that were measured using the Bull et al., (1996). This scale has six dimensions of psychology skills. After finishing their training sessions, the experimental group played 12 social recreational games for 20–30 minutes, three times per week for eight weeks. Results. There was a significant difference in the means of scores of psychology skills in the experimental and control groups before and after intervention (p < 0.05). However, the difference in improvement was in favor of the experimental group as it ranged from (31.562 to 43.897). In contrast, it ranged from (30.666 to 37.988) in the control group, and there was a statistically significant difference in the two groups’ post-test scores (t = 11.533; p < 0.05). Conclusion. Playing social recreational games improved wheelchair tennis players’ psychological skills. The current study provided coaches and trainers with a clear recreational training model.